Meningkatkan Hasil Belajar PAI Dengan Menggunakan Metode Diskusi Di Kelas IV SD Negeri 11 Tanjung Gadang - Rahmi, Ilfika (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to improve students’ learning outcomes through the implementation of constructivism-based learning strategies. The research method employed is Classroom Action Research (CAR) conducted in two cycles. Each cycle consisted of planning, implementation, observation, and reflection stages. The findings reveal that in the first cycle, students’ motivation and participation increased, although learning outcomes were not yet optimal. After reflections and improvements in the second cycle, students’ learning outcomes significantly improved, with most students meeting the minimum mastery criteria. This success is supported by constructivism theory, emphasizing the importance of collaborative activities and student-centered learning. In conclusion, this strategy is effective in enhancing learning outcomes and is recommended for consistent application in classrooms.